The Effect of Implementing Problem-Based Learning (PBL) Model Assisted by Problem-Based LKPD on Students' Learning Outcomes in Motion Systems Material - Afni Nurjanah; Cicik Suriani (Universitas Islam Negeri Walisongo Semarang, 2025)
This study aims to determine the effect of the Problem-Based Learning (PBL) model assisted by problem-based worksheets on the learning outcomes and cognitive abilities of students in the motion system subject in class XI at SMA Negeri 1 Bahorok in the 2025/2026 academic year. This quasi-experimental study with a pretest and posttest control group design involved 72 students selected through simple random sampling. Class XI-1, as the experimental group, received PBL learning assisted by problem-based worksheets, while class XI-3, as the control group, received direct learning (lectures). The results of the study showed an increase. The average score increased from 37.31 to 72.78 in the experimental class (61.11% mastery) and from 41.11 to 55.00 in the control class (19.44% mastery). Overall, the N-Gain of the experimental class was g = 0.57 (57%, moderate), higher than that of the control class, g = 0.23 (23%, low). At the C4-C6 cognitive level, the experimental class showed N-Gain C4 = 0.60 (60%, moderate), C5 = 0.51 (51%, moderate), and C6 = 0.70 (70%, high)—consistently exceeding the control class (C4 = 0.30; C5 = 0.16; C6 = 0.09). Thus, the application of PBL assisted by problem-based LKPD had a positive effect on the learning outcomes and cognitive abilities of students.